Corporate performance criteria in Thailand: individual perceptions of company directors' tasks and roles - Boriboonsate, P.; Dickie, Laurence (International Academy of Business and Economics, 2010)
In more than 10 years since the financial crisis in Thailand in 1997, weaknesses in corporate governance have been identified as a major cause of the crisis. Thus, increased attention in the country has been paid to corporate governance reform and the roles of corporate boards of directors in relation to corporate performance. This paper is used to report on a study which examined the emphases that Thai directors place on corporate performance criteria, their individual tasks as board members and the extent to which they consider themselves to have a defined functional role. The study employed a quantitative approach based on questionnaires surveying 195 Thai directors of companies listed on the Stock Exchange of Thailand (SET) across various industries in the year 2009. It was found that the emphasis placed by directors on most corporate performance criteria, especially the financial aspect, was related to the degree to which they saw themselves in a monitoring role. Moreover, rather than general perceived roles, specific task involvement was more closely related to the performance criteria emphasised by directors. For practitioners, academics and policy makers, results raise awareness of directors' practices in the area of corporate governance and suggest a set of director tasks that are required for companies to achieve growth.